A comparative study of mini-monovision, crossed mini-monovision, and emmetropia with enhanced monofocal intraocular lenses - Yoshifumi Fujita; Yuya Nomura; Emi Itami; Tetsuro Oshika (Scientific Reports)
Abstract We compared the visual performance and subjective outcomes of mini-monovision, crossed mini-monovision, and bilateral emmetropia using enhanced monofocal intraocular lenses (IOLs). This retrospective study involved 200 eyes of 100 patients who underwent surgery for bilateral age-related cataract using an enhanced monofocal IOL (TECNIS Eyhance). The dominant eye was identified before surgery. Based on patients’ preferences, they were divided into mini-monovision (dominant eye for distance and non-dominant eye for near with 1.0 D anisometropia), crossed mini-monovision (dominant eye for near and non-dominant eye for distance with 1.0 D anisometropia), or bilateral emmetropia groups. There were 32 patients in the mini-monovision group, 28 in the crossed mini-monovision group, and 40 in the emmetropia group. While binocular distance visual acuity was not different among groups, intermediate and near visual acuity was significantly better in the mini-monovision and crossed mini-monovision groups than in the emmetropia group (p < 0.001). The severity of glare and halo, as well as the level of patient satisfaction, did not differ between groups. The rate of spectacle independence was significantly higher in the mini-monovision and crossed mini-monovision groups than in the emmetropia group (p = 0.008). Mini-monovision and crossed mini-monovision approaches using enhanced monofocal IOLs are equally effective in enhancing intermediate and near vision without compromising distance vision, leading to reduced spectacle dependence.